Type-B Energetic Processes and Their Associated Scientific Implications - Lee, James Weifu (Journal of Scientific Exploration, 2022)
Recently, our work has identified two thermodynamically distinct types (A and B) of energetic processes naturally occurring on Earth: Type-A energy processes such as the classical heat engines, ATP hydrolysis, and many of the known chemical, electrical, and mechanical processes apparently well follow the second law of thermodynamics; and Type-B energy processes, such as the newly discovered thermotrophic function that isothermally utilizes environmental heat energy to do useful work in driving ATP synthesis, which follows the first law of thermodynamics (conservation of mass and energy), but does not necessarily have to be constrained by the second law, owing to their special asymmetric functions. In mitochondria, their special asymmetric functions associated with Type-B processes comprise: 1) The transmembrane asymmetry of inner mitochondrial membrane structure with the protonic outlets of redox-driven proton-pumping protein complexes protruded away from the membrane surface by about 1-3 nm into the bulk liquid p-phase while the protonic inlet of the F0F1-ATP synthase located rightly at the transmembrane electrostatically localized proton (TELP) layer; and 2) The lateral asymmetry of mitochondrial cristae with an ellipsoidal shape that enhances the density of TELP at the cristae tips where the F0F1-ATP synthase enzymes are located in supporting the TELP-associated thermotrophic function. The identification of Type-B energy processes indicates that there is an entirely new world of physical and energy sciences yet to be fully uncovered. Innovative efforts on Type-B processes to enable isothermally utilizing endless environmental heat energy could help to liberate all peoples from their dependence of fossil fuel energy, thus helping to reduce greenhouse gas CO2 emissions and control climate change toward a sustainable future for the humanity on Earth.